Comparison of HE4, CA125, and ROMA Diagnostic Accuracy: A Prospective and Multicenter Study for Chinese Women With Epithelial Ovarian Cancer. Issue 52 (December 2015) - Zhang, Pengjun; Wang, Chuanxin; Cheng, Liming; Zhang, Peng; Guo, Lin; Liu, Wanli; Zhang, Zhongying; Huang, Yanchun; Ou, Qishui; Wen, Xinyu; Tian, Yaping
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Risk of Ovarian Malignancy Algorithm (ROMA) combing human epididymis secretary protein 4 (HE4) and CA125 showed better diagnostic accuracy for epithelial ovarian cancer (EOC) when compared with HE4 or CA125 alone; however, other studies showed no or worse diagnostic accuracy. We aim to conduct a prospective and multicenter clinical trial to compare the diagnostic accuracy of HE4, CA125, and ROMA for EOC. A prospective and multicenter (n = 9) trial including 2481 individuals was performed in Chinese women. HE4, CA125, and ROMA diagnostic accuracy were evaluated according to different menopausal status and stages of EOC. Their diagnostic values were evaluated by the area under curve (AUC) and compared by the Z scores. Diagnostic specificity of other kinds of participants (n = 1098) was also evaluated. For discriminating between healthy control (HC) and EOC, only CA125 showed significant difference for discriminating HC and EOC in all the individuals when compared with HE4 and ROMA ( P  < 0.001 and P  = 0.02, respectively), at the cutoff value of 31.5, the sensitivity (SN) and specificity (SP) were 88.6% and 97.1%. For discriminating between benign pelvic mass (BPM) and EOC, ROMA showed significant difference for discriminating BPM and EOC in the all individuals ( P  = 0.01 and P  = 0.02, respectively) and the postmenopausal individuals ( P  = 0.03 and P  = 0.04, respectively), at the cutoff value of 27.3 and 34.5, the SNs were 97.0% and 89.4%, SPs were 81.4% and 82.5%, separately. Within all kinds of diseases, there was no significant difference in specificity between CA125 and HE4. In conclusions, when HE4, CA125, and ROMA were compared with each other according to different menopausal status, and stages. Only CA125 showed significant difference for discriminating HC and EOC in all the individuals, and ROMA for discriminating BPM and EOC in the all individuals and postmenopausal individuals when compared with HE4 or CA125. HE4 has showed no significant difference in specificity with all kinds of diseases when compared with CA125.